Spent Mushroom Compost of Pleurotus ostreatus: A Tool to Treat Soil Contaminated with Endosulfan. Issue 4 (2nd October 2019) - Sadiq, Saima; Mahmood-ul-Hassan, M.; Rafiq, Nazia; Ahad, Karam
Abstract: Composts especially spent mushroom composts (SMC) have been used for their ability to degrade toxic organic pollutants. Due to extreme toxicity, endosulfan (C9 H6 Cl6 O3 S) is categorized as a Category 1 pollutant by the U.S. EPA because of its well-reported carcinogenicity. This study was done to monitor the biodegradation potential of SMC against this pesticide. For this purpose, bioreactors (BRs) system was designed to mimic the field conditions. Soil within all four BRs contaminated with endosulfan was amended with four different treatments of SMC. Quantitative reduction in amount of endosulfan isomers was calculated using Gas Chromatography–Electron Capture Detector. For the monitoring of metabolites formed as a result of biodegradation, Gas Chromatography–Mass Spectrometry was used. Maximum attenuation was observed in BR1 (fresh SMC and soil). In BR2 when fresh SMC was added in sterilized soil, rate of removal was declined as compared to BR1 . In another bioreactor BR3, where unsterilized soil was used with sterilized SMC, total reduction in quantity of endosulfan was less than BR1 and BR2 . BR4 (abiotic control) showed the least reduction suggesting the role of SMC and soil microbes. Degradation was well described using simple first-order kinetics which revealed that the active microcosm of BR1 manifested least DT50 . Denaturation of either SMC(BR3 ) or soil(BR2 ) or both (BR4 ) resulted in less biodegradation than BR1 .